The effects of GRIN2B and DRD4 gene variants on local functional connectivity in attention-deficit/hyperactivity disorder - Kim, Johanna Inhyang; Yoo, Jae Hyun; Kim, Dohyun; Jeong, Bumseok; Kim, Bung-Nyun (Brain imaging and behavior, 2018)
Based on the interplay between dopaminergic and glutamatergic systems, N-Methyl-D-Asparate (NMDA) receptor genes are thought to be involved in the pathophysiology of ADHD. However, the phenotypical correlates of brain functions associated with NMDA receptor genes and dopamine receptor genes in ADHD are yet to be investigated. We examined the diagnosis, genotype and the diagnosis-genotype interaction effects of GRIN2B and DRD4 variants on the local functional connectivity (by using the mean of static regional homogeneity (ReHo) and the mean and standard deviation (SD) of dynamic ReHo) in 67 ADHD subjects and 44 controls (aged 6–17 years). GRIN2B genotypes were divided into the C/C group and T allele carrier group; DRD4 genotypes were divided into the 2R group and non-2R group. The correlation between the ReHo values showing significant diagnosis-genotype interaction and Children’s Color Trails Test (CCTT) scores were examined. CCTT measures processing speed, sustained and divided attention. There were significant diagnosis ( p < 0.001) and interaction ( p = 0.02) effects of the GRIN2B variant on the static ReHo mean in the left superior parietal cluster, and the ReHo value was positively correlated with the CCTT interference score in the ADHD with T allele carrier subgroup ( p = 0.012). There were significant diagnosis ( p < 0.001) and interaction ( p = 0.03) effects of the DRD4 variant on the dynamic ReHo SD in the right superior parietal cluster. These results suggest that alterations in the glutamate and dopamine system in ADHD may contribute to abnormalities in local functional connectivity and its dynamic repertoire in the superior parietal area, and these abnormalities would be related to dysfunction in sustained and divided attention.